Green bioprinting: Viability and growth analysis of microalgae immobilized in 3D‐plotted hydrogels versus suspension cultures. Issue 7 (30th March 2015) - Krujatz, Felix; Lode, Anja; Brüggemeier, Sophie; Schütz, Kathleen; Kramer, Julius; Bley, Thomas; Gelinsky, Michael; Weber, Jost
<x xml:space="preserve">Abstract</x> In this study, microalgae were cultivated in the form of suspension cultures and a new structurally organized immobilization technique called "Green Bioprinting." This technique allows the cocultivation of microorganisms in close vicinity to, but without direct contact with microalgae, to improve the oxygen supply of different cell types by photosynthetic oxygen evolution. However, more research on the optimum culture conditions for immobilized microalgae is necessary. Therefore, Chlamydomonas reinhardtii 11.32b and Chlorella sorokiniana UTEX1230 were suspended in culture medium or embedded in hydrogels by the 3D‐bioprinting process followed by cultivation under different temperatures (26°C, 30°C, or 37°C) and modes of illumination (continuous illumination or a 14/10 h light/dark cycle). The viability was monitored by either flow cytometry (suspension cultures) analysis of DiBAC4(3)‐stained cells or fluorescence image analysis (hydrogel‐embedded cultures). Suspended microalgae subjected to continuous illumination exhibited an increased number of membrane‐depolarized cells compared to those cultivated at a 14/10 h light/dark cycle. Hydrogel immobilization resulted in a facilitated viability and stable growth rates between 0.4 and 0.7 d−1 for both microalgae strains. Concluding, the 3D‐bioprinting immobilization represents a technique to cultivate microalgae at a high viability and growth rate even under nonoptimal temperature conditions.